2019
DOI: 10.3390/antiox9010022
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Terpenoids-Rich Padina pavonia Extract Attenuates Hyperglycemia, Insulin Resistance and Oxidative Stress, and Upregulates PPARγ in a Rat Model of Type 2 Diabetes

Abstract: Seaweeds are rich in structurally diverse bioactive compounds with promising therapeutic effects. This study aimed to isolate and identify terpenes from the brown alga Padina pavonia and to investigate its antidiabetic activity, pointing to the possible involvement of peroxisome proliferator-activated receptor (PPAR)γ. Type 2 diabetes was induced by feeding rats a high fat diet (HFD) for 4 weeks followed by injection of 35 mg/kg streptozotocin (STZ). The diabetic rats received P. pavonia extract (PPE; 50, 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 91 publications
(115 reference statements)
1
18
0
Order By: Relevance
“…Malik et al stated that oxidative stress caused by hyperglycemia due to the overproduction of mitochondrial reactive oxygen species (ROS) is involved in this process (Brownlee, 2001;Czajka & Malik, 2016;Nishikawa et al, 2000). Excessive ROS production mediates oxidative stress in DM by high glucose and/or fatty acid oxidation (Germoush et al, 2019). Lu et al demonstrated that the main mediator against diabetic complications is oxidation stress (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Malik et al stated that oxidative stress caused by hyperglycemia due to the overproduction of mitochondrial reactive oxygen species (ROS) is involved in this process (Brownlee, 2001;Czajka & Malik, 2016;Nishikawa et al, 2000). Excessive ROS production mediates oxidative stress in DM by high glucose and/or fatty acid oxidation (Germoush et al, 2019). Lu et al demonstrated that the main mediator against diabetic complications is oxidation stress (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that oxidative stress plays a pivotal role in the development of diabetes-induced behavioral and cognitive defects. [3][4][5] The brain is highly sensitive to oxidation because of the presence of large amounts of unsaturated fatty acids and oxygen, which serve as a substrate for lipid peroxidation. The peroxidation products are the biomarkers of oxidative stress in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, cognitive decline is also one of the complications associated with such a lifestyle and habits but it has been studied relatively less. Increasing evidence has suggested that oxidative stress plays a pivotal role in the development of diabetes‐induced behavioral and cognitive defects 3–5 . The brain is highly sensitive to oxidation because of the presence of large amounts of unsaturated fatty acids and oxygen, which serve as a substrate for lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations